Blindingly obvious and frequently exploitable: Money laundering through the purchasing of high-value portable commodities. Issue 2 (2nd May 2017) - Gilmour, Nicholas
Abstract : Purpose: The purpose of this paper is to provide an understanding of the openness and specific techniques through which illicit funds generated by criminals are moved, transferred and laundered in the financial arrangement retained using high-value portable commodities in the UK and internationally. Design/methodology/approach: This paper presents exploratory findings from research conducted between 2011 and 2013 in the UK. The research undertaken sought to identify the process, steps and vulnerabilities behind money laundering via high-value portable commodities and highlight the explicit facilitators enabling this method of money laundering to take place. Findings: Despite significant research into money laundering typologies, the use of high-value portable commodities has remained largely untouched regardless of the increased implementation of anti-money laundering policies and procedures seeking to halt the depositing of illicit cash into the global financial system. This paper demonstrates how high-value portable commodities are extremely vulnerable to money laundering despite the large-scale anti-money laundering efforts focused on combating money laundering across a broad range of sectors. Research limitations/implications: This paper is of value to government policymakers, regulators and financial institutions considering future preventative measures. It is also of value to financial investigators and law enforcement agencies intent on investigating money laundering. While the paper relies on data from the UK, the overall findings are such that wherever high-value portable commodities are present, so too does the opportunity for money laundering through the financial arrangement retained by high-value portable commodities. Originality/value: This paper presents new research on the direct link between high-value portable commodities and money laundering in the UK despite significant research having previously taken place to identify and develop money laundering typologies.